Structure of N-(3, 4-Dimethoxyphenyl)pyrido[3′, 2′:4, 5]-thieno[3, 2-d]pyrimidin-4-amine, a New Inhibitor of CLK1 and DYRK1A Kinases. (23rd December 2013) - Guillon, Jean; Marchivie, Mathieu; Loidreau, Yvonnick; Pinaud, Noël; Besson, Thierry
Abstract : The complete crystal structure of N -(3, 4-dimethoxyphenyl)pyrido[3′, 2′:4, 5]thieno[3, 2- d ]pyrimidin-4-amine, synthesized via a Dimroth rearrangement and designed as new inhibitor of CLK1 and DYRK1A kinases, was established by a single-crystal X-ray diffraction. The crystal is orthorhombic, space group P ca21 ;a = 13.1593 ( 9 ), b = 13.9823 ( 10 ), c = 8.5403 ( 7 ) Å, α = β = γ = 90 °, V = 1571.4 ( 2 ) Å 3, andZ = 4, C17 H14 N4 O2 S. Solid-state data could be used to enlighten the biological mechanism of action.